Evaluation method for cutting performance of ceramic plate and application
By detecting the vertical center bending and water absorption of ceramic plates and calculating the cutting cracking rate, the problem of inaccurate detection of cutting performance of ceramic plates is solved, and higher evaluation accuracy and processing performance improvement are achieved.
Patent Information
- Application Number
- CN202410291968.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-14
- Publication Date
- 2024-12-27
AI Technical Summary
The existing methods for cutting performance detection of ceramic plates are not accurate enough to effectively evaluate the cutting performance of ceramic plates, resulting in the inability to determine whether the finished product has good cutting performance.
By testing the vertical center bending and water absorption of ceramic plates, combining the water absorption after thinning treatment, the cutting cracking rate is calculated, the cutting performance of ceramic plates is reflected on the side, and the formula and firing parameters of ceramic plates are adjusted to improve cutting performance .
It improves the accuracy of the evaluation of the cutting performance of ceramic plates and is suitable for different batches of ceramic plates, ensuring that they avoid cracks during the cutting process and improving processing performance.
Smart Images

Figure BDA0004741018130000071 
Figure BDA0004741018130000081 
Figure BDA0004741018130000082
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ceramic plate performance evaluation, and in particular to a method for evaluating the cutting performance of a ceramic plate and its application. Background Art
[0002] With the development of ceramic production technology, large-sized ceramic panels have become more and more popular among consumers in recent years, and the application areas of ceramic panels have been continuously expanded, from traditional wall floors, outdoor panels to countertops, cabinets and other home furnishing fields.
[0003] As the use of ceramic panels becomes wider and wider, people have higher and higher requirements for their processing performance and use performance, especially requiring them to have better cutting (drilling) processing performance. This is mainly because with the increase in the use scenarios of ceramic panels, when users lay them in home decoration and other scenarios, due to size limitations, ceramic panels often need to be cut to meet size requirements. However, so far, there is no more accurate cutting performance detection method for ceramic panels, resulting in the inability to clearly know whether the finished ceramic panels have good cutting performance. Usually, it can only be known when they are actually cut by a bridge cutting machine, a vertical cutting machine, or a water jet cutting machine to cut various shapes and patterns. The cutting speed of the above equipment, the difference in blades, etc. will affect the accuracy of the test results. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for evaluating the cutting performance of ceramic plates and its application, aiming to improve the technical problem that there is no relatively accurate method for evaluating the cutting performance of existing ceramic plates and it is impossible to accurately know the quality of their cutting performance.
[0005] To achieve the above object, the present invention provides a method for evaluating the cutting performance of a ceramic plate, comprising the following steps:
[0006] S1. Detecting the vertical center curvature of the ceramic plate;
[0007] S2. Grinding the ceramic plate to thin it, and detecting the water absorption rate of the ceramic plate after the grinding and thinning process;
[0008] S3. Obtain the cutting cracking rate of the ceramic plate according to the water absorption rate of the ceramic plate and / or the vertical center curvature of the ceramic plate.
[0009] The cutting performance of ceramic plates such as rock plates is a very important internal indicator. Determining the cutting performance of ceramic plates facilitates subsequent cutting. In this solution, since the vertical center curvature of the ceramic plate truly reflects the bonding of the body and glaze, the matching of the expansion coefficient, the sintering degree of the product, the rationality of the kiln firing system and other issues, the cutting performance of the ceramic plate is reflected indirectly by testing the water absorption rate and / or the vertical center curvature of the ceramic plate to determine whether the different batches of ceramic plates produced are suitable for cutting. This evaluation method has a high accuracy and can better reflect the cutting performance of the ceramic plate.
[0010] The vertical center curvature of the ceramic plate is large, and when the water absorption rate is higher, it is more likely to produce cutting cracks. Among them, this scheme is to detect the water absorption rate of the ceramic plate after it is ground thin. Since the sintering process is gradually progressing from the surface of the ceramic plate to the inside of the ceramic plate, the water absorption rate detection of the traditional ceramic plate is only a relatively rough detection of its overall (surface) water absorption rate. However, if the water absorption rate of the ceramic plate is less than 0.05% when detected by the traditional method, the water absorption rate inside the ceramic plate may be above 0.10-0.35%, or even higher. At this time, the degree of sintering inside and outside the ceramic plate is seriously uneven, resulting in uneven stress inside the ceramic plate, which will also cause cutting cracks. Therefore, this scheme chooses the water absorption rate after thinning detection, which can better reflect the cutting performance of the ceramic plate from the side, and has higher accuracy.
[0011] Among them, the cutting crack rate (Q) of the ceramic plate refers to the sampling cutting in a batch of ceramic plates, Q = (the number of plates with cutting cracks / the total number of cut plates) × 100%, the water absorption rate is directly measured by the instrument, and the vertical center curvature refers to the center curvature measured when the ceramic plate is placed vertically.
[0012] Preferably, when the water absorption rate of the ceramic plate after grinding is ≤0.15%, the cutting cracking rate Q of the ceramic plate is ≤5%;
[0013] When the water absorption rate of the ceramic plate after grinding is less than 0.15% and less than 0.2%, the cutting cracking rate Q of the ceramic plate is 5-15%;
[0014] When the water absorption rate of the ceramic plate after grinding is less than 0.27%, the cutting cracking rate Q of the ceramic plate is 15-30%;
[0015] When the water absorption rate of the ceramic plate after grinding is less than 0.27% and less than 0.35%, the cutting cracking rate Q of the ceramic plate is 30-50%;
[0016] When the water absorption rate of the ceramic plate after being ground thin is ≥0.35%, the cutting cracking rate Q of the ceramic plate is >50%.
[0017] The above is the measured correspondence between the water absorption rate of the ceramic plate after thinning and the cutting cracking rate. After verification by data from actual cutting of different batches of ceramic plates, the above correspondence between the water absorption rate and the cutting cracking rate is relatively accurate, and the different levels of its cutting performance can be roughly determined based on the water absorption rate of the ceramic plate.
[0018] Preferably, when the vertical center curvature of the ceramic plate is ≤1.5 mm, the cutting cracking rate Q of the ceramic plate is ≤5%;
[0019] When the vertical center curvature of the ceramic plate is less than 1.5 mm and less than 2.0 mm, the cutting cracking rate Q of the ceramic plate is 5-20%;
[0020] When the vertical center curvature of the ceramic plate is 2.0 mm or less and the cutting cracking rate Q of the ceramic plate is 20-50%;
[0021] The vertical center curvature of the ceramic plate is ≥2.5 mm, and the cutting cracking rate Q of the ceramic plate is >50%.
[0022] Similarly, the above is the correspondence between the vertical center curvature of the ceramic plate and the cutting cracking rate, which is also relatively accurate and provides a second side evaluation method for the cutting performance of the ceramic plate, which has a wider range of applications. In this solution, the vertical center curvature is an absolute value, that is, whether the brick shape of the ceramic plate is bent in the positive direction or the reverse direction, it is counted as a positive number.
[0023] In this evaluation method, both the vertical center curvature and water absorption can be tested. When the water absorption of the ceramic plate after grinding is controlled at 0.15% or less, and the vertical center curvature is controlled at 1.5mm or less, the actual sintering degree inside the product is high, the matrix is relatively uniform, and the internal stress is small, which can basically avoid cutting cracking problems. The cutting cracking rate of the ceramic plate is ≤3%.
[0024] Preferably, in step S1, after the ceramic plate is ground thin, the water absorption rate at the four corners and the center is detected, and the average value is the water absorption rate of the ceramic plate. The water absorption rate detection of the ceramic plate in this scheme refers to testing the four corners and the middle position of a randomly selected ceramic plate after the plate is ground thin, and the water absorption rate of the ceramic plate is determined simultaneously, which has higher accuracy. The middle position is the area near the intersection of the two diagonals of the ceramic plate.
[0025] Preferably, in step S1, the front and back sides of the ceramic plate are both ground thinner by 1-3 mm. When evaluating the cutting performance, the front and back sides of the ceramic plate can be ground thinner by, for example, 1 mm, 2 mm, 3 mm, etc. Specifically, in actual production, a 12 mm thick ceramic plate can be ground thinner to 8.8-9.2 mm; a 9 mm thick ceramic plate can be ground thinner to 5.8-6.2 mm.
[0026] Preferably, the area of the ceramic plate is 2m 2 The evaluation method of this scheme can better adapt to the single piece area of 2m 2 The rectangular ceramic plate mentioned above may specifically have a size (length and width) of 2400×1200 mm, 1200×2700 mm, 1600×3200 mm, etc. Of course, ceramic plates of other shapes may also be applicable.
[0027] In addition, the present invention also proposes an application of an evaluation method as described in any of the above items in the production of ceramic plates. When the water absorption rate of the ceramic plate after grinding is ≥0.35%, or the vertical center curvature of the ceramic plate is ≥2.5mm, the cutting performance of the ceramic plate is poor. In order to improve the cutting performance of the ceramic plate, the formula of the ceramic plate is adjusted to promote the formation of mullite and avoid the cutting cracking of the ceramic plate. Specifically, by weight, the formula of the ceramic plate can be adjusted to: 40-60 parts of low-temperature sand, 3-5 parts of ultra-white sand, 3-8 parts of bentonite, 0-8 parts of talc, 20-35 parts of ball clay, 10-18 parts of high-alumina sand, 2-15 parts of high-potassium stone and 0-2 parts of composite zirconium. Among them, composite zirconium refers to a substance mainly containing aluminum oxide, zirconium silicate and / or other materials, which can play a role in whitening and increasing the firing temperature.
[0028] Preferably, the chemical composition of the ceramic plate is: SiO2 65.5-67.3%, Al2O3 20.7-22.2%, MgO0.06-0.5%, CaO 0.1-0.5%, K2O 2.2-2.9%, Na2O 2.8-3.5%, LOI 5.2-5.9% and ZrO20-0.6%. The chemical composition of the above formula is more suitable within this range, and it is not easy to cause large fluctuations in the firing temperature of the formula during processing. Among them, the limitation of sodium content is more important, and the content of Na2O in sodium oxide needs to be maintained at about 2.8-3.5%, otherwise, the ceramic plate obtained in the same way is also prone to cutting cracks.
[0029] In addition, the above ceramic plates may contain 0-0.6% of other impurities.
[0030] Preferably, when the water absorption rate of the ceramic plate is ≥2.5mm, or the vertical center curvature of the ceramic plate is ≥2.5mm, the firing parameters of the ceramic plate are synchronously adjusted to a maximum firing temperature of 1175-1185°C and a firing time of 90-130min. A reasonable firing system (cooling system) can also promote the production of mullite and the uniformity of the internal matrix. After the firing temperature of the kiln in this solution is controlled within the above range, the ceramic plate can be slightly over-fired, which can well avoid the problem of cutting cracks.
[0031] Preferably, when the water absorption rate of the ceramic plate is ≥2.5 mm, or the vertical center curvature of the ceramic plate is ≥2.5 mm, the green expansion coefficient of the ceramic plate is adjusted to 180-230*10 -6 / ℃; the glaze expansion coefficient of the ceramic plate is controlled at 170-220*10 -6 / ℃ (the body and glaze are matched, the difference in linear expansion coefficient at 500℃*30≤10), which improves the difference in expansion coefficient between the body and glaze, and is beneficial to improving the processing performance of ceramic plates. Among them, the expansion coefficient values of 180-230 and 170-220 refer to the values obtained by the linear expansion coefficient of the body / glaze at 500℃*30.
[0032] Compared with the prior art, the method for evaluating the cutting performance of ceramic plates and the application of the present invention have the following beneficial effects:
[0033] 1. This scheme indirectly reflects the cutting performance of ceramic plates by testing the water absorption rate and / or vertical center curvature of ceramic plates in two different directions, so as to determine whether different batches of ceramic plates produced are suitable for cutting. This evaluation method has high accuracy and can be applied to various types of ceramic plates, and can better reflect the cutting performance of ceramic plates.
[0034] 2. In addition, this plan has made adjustments for ceramic plates with poor cutting performance, mainly by limiting the formula, chemical composition, firing system and the difference in the expansion coefficient of the body and glaze of the ceramic plates (specifically by adjusting the expansion coefficient of the body / glaze to make the two closer and more matched), so that the ceramic plates can have better cutting performance. DETAILED DESCRIPTION
[0035] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0037] A method for evaluating the cutting performance of a ceramic plate comprises the following steps:
[0038] S1. Detecting the vertical center curvature of the ceramic plate;
[0039] S2. Grind the ceramic plate thinly, thinning the front and back sides of the ceramic plate by 1-3 mm; detect the water absorption rate of the ceramic plate after the grinding process, wherein the water absorption rate at the four corners and the center is detected, and the average value is the water absorption rate of the ceramic plate;
[0040] S3. Obtaining the cutting cracking rate of the ceramic plate according to the water absorption rate of the ceramic plate and / or the vertical center curvature of the ceramic plate;
[0041] Specifically, when the water absorption rate of the ceramic plate after grinding is ≤0.15%, the cutting cracking rate Q of the ceramic plate is ≤5%; when the water absorption rate of the ceramic plate after grinding is 0.15%<0.2%, the cutting cracking rate Q of the ceramic plate is 5-15%; when the water absorption rate of the ceramic plate after grinding is 0.2%≤0.27%, the cutting cracking rate Q of the ceramic plate is 15-30%; when the water absorption rate of the ceramic plate after grinding is 0.27%≤0.35%, the cutting cracking rate Q of the ceramic plate is 30-50%; when the water absorption rate of the ceramic plate after grinding is ≥0.35%, the cutting cracking rate Q of the ceramic plate is>50%;
[0042] When the vertical center curvature of the ceramic plate is ≤1.5mm, the cutting cracking rate Q of the ceramic plate is ≤5%; when the vertical center curvature of the ceramic plate is 1.5mm<the vertical center curvature of the ceramic plate<2.0mm, the cutting cracking rate Q of the ceramic plate is 5-20%; when the vertical center curvature of the ceramic plate is 2.0mm≤the vertical center curvature of the ceramic plate<2.5mm, the cutting cracking rate Q of the ceramic plate is 20-50%; when the vertical center curvature of the ceramic plate is ≥2.5mm, the cutting cracking rate Q of the ceramic plate is>50%.
[0043] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0044] The specifications of the ceramic plates in the following embodiments / comparative examples are: 2400 mm in length, 1200 mm in width, and 10 mm in thickness. In other embodiments, the size of the ceramic plates can be adaptively adjusted. The following ceramic plates are produced by Guangdong Jinyitao Ceramics Group Co., Ltd. Different water absorption rates or different vertical center curvatures represent that the ceramic plates are produced from different batches.
[0045] Example 1
[0046] A method for evaluating the cutting performance of a ceramic plate comprises the following steps:
[0047] S1. The ceramic plate is ground thin, and the front and back sides of the ceramic plate are ground thin by 1.5 mm, that is, the thickness of the ceramic plate after grinding is 7 mm;
[0048] S2. Detect the average water absorption rate of the four corners and the center of the ceramic plate after the grinding treatment. The average value is the water absorption rate of the ceramic plate;
[0049] S3. Obtain the cutting cracking rate of the ceramic plate according to the water absorption rate of the ceramic plate (indicated by X in the following table).
[0050] The specific relationship between water absorption and cutting cracking rate is shown in the following table. This solution also cuts ceramic plates of different water absorption product batches actually produced and records the actual cutting cracking conditions:
[0051]
[0052] Note: The specific cutting process and parameters of the above-mentioned ceramic plate are as follows: the ceramic plate is cut by a five-axis water jet device, water and pomegranate sand are used as the medium, the pomegranate sand shape number is 80 mesh, the sandblasting port diameter is 2.5 mm, the implementation standard is JB / T8337-2012, the cutting rate is 900 mm / min, the pressure is 4000 bar, the ceramic plate is placed flat on the water jet platform for alignment, the specified graphics to be cut are input on the computer, and long strip patterns and special-shaped patterns (ovals, hexagons, trapezoids, diamonds, etc.) are cut on each ceramic plate. After the cutting is completed, check whether the ceramic plate is cracked. If the edges are neat and smooth, there are no cutting cracks, no bursting, and no chipping, it is determined that no cutting cracks are generated (qualified), and the actual cracking rate = (the amount of plates with cutting cracks / the total amount of plates cut) × 100%, the total cutting amount of each batch of ceramic plates is 40 pieces, and the total cutting amount of the following embodiments / comparative examples is 40 pieces.
[0053] It can be seen from the test results in the above table that the evaluation method of this scheme has a small deviation from the actual cutting cracking rate of ceramic plates and a high accuracy, which can reflect the cutting performance of ceramic plates of different batches at corresponding levels.
[0054] Comparative Example 1
[0055] The batches of ceramic plates in this comparative example are all the same as those in Example 1, except that they have not been subjected to a thinning treatment. The specific water absorption rate, cutting cracking rate and actual cutting cracking conditions are shown in the following table:
[0056]
[0057]
[0058] It can be seen from the test data in the above table that directly testing the water absorption rate of ceramic plates to obtain their cracking rate will have a large error and cannot accurately characterize the cutting performance of ceramic plates.
[0059] Example 2
[0060] A method for evaluating the cutting performance of a ceramic plate comprises the following steps:
[0061] S1. The vertical center curvature of the ceramic plate without thinning treatment;
[0062] S2. Obtain the cutting cracking rate of the ceramic plate according to the vertical center curvature of the ceramic plate (denoted by S in the following table).
[0063] The specific correspondence between the vertical center curvature and the cutting cracking rate is shown in the following table. This solution also cuts each batch of ceramic plates and records the actual cutting cracking conditions:
[0064]
[0065]
[0066] It can be seen from the test results in the above table that in the evaluation method of this scheme, the deviation between the cutting cracking rate predicted by the vertical center curvature of the ceramic plate and the actual cutting cracking rate is also very small, which is basically within the range of the above evaluation method, with high accuracy, and can better reflect the cutting performance of corresponding grades of ceramic plates of different batches.
[0067] Example 3
[0068] A method for evaluating the cutting performance of a ceramic plate comprises the following steps:
[0069] S1. The ceramic plate is ground thin, and the front and back sides of the ceramic plate are ground thin by 1 mm, that is, the thickness of the ceramic plate after grinding is 8 mm;
[0070] S2. Detect the water absorption rate of the ceramic plate after the grinding and thinning treatment and the vertical center curvature of the ceramic plate without the grinding and thinning treatment;
[0071] S3. Obtain the cutting cracking rate of the ceramic plate according to the water absorption rate and the vertical center curvature of the ceramic plate.
[0072] The specific correspondence between water absorption rate, vertical center curvature and cutting cracking rate is shown in the following table. This scheme also cuts each batch of ceramic plates and records the actual cutting cracking situation:
[0073]
[0074] It can be seen from the test results in the above table that by controlling the water absorption rate of the ceramic plate after grinding to below 0.15% and the vertical center curvature to below 1.5mm, the cutting cracking problem can be avoided as much as possible. The cutting cracking rate of the ceramic plate determined by this evaluation method is within 3%.
[0075] For the ceramic plate of the above batch 20210719-1 (i.e., Example 1-11), its cutting performance is poor, the water absorption rate after thinning is ≥0.35%, and the vertical center curvature of the ceramic plate is ≥2.5mm (3.1mm), and the cutting cracking rate Q is above 50%.
[0076] Therefore, for the above-mentioned ceramic plates with poor cutting performance (Examples 1-11), the original formula is: 35 parts of low-temperature sand, 3 parts of ultra-white sand, 12 parts of bentonite, 5 parts of talc, 10 parts of ball clay, 15 parts of high-alumina sand, 18 parts of high-potassium stone and 2 parts of composite zirconium. The corresponding chemical composition of this formula is: SiO2 63.5%, Al2O3 23.68%, MgO 0.1%, CaO 0.38%, K2O5.8%, Na2O1.3% and LOI 4.78%, ZrO2 0.35%, and other (impurities) 0.11%.
[0077] This solution can adjust the original formula of the green body to: 40-60 parts of low-temperature sand, 3-5 parts of ultra-white sand, 3-8 parts of bentonite, 0-8 parts of talc, 20-35 parts of ball clay, 10-18 parts of high-alumina sand, 2-15 parts of high-potassium stone and 0-2 parts of composite zirconium. The chemical composition corresponding to this formula is: SiO2 65.5-67.3%, Al2O3 20.7-22.2%, MgO 0.06-0.5%, CaO 0.1-0.5%, K2O 2.2-2.9%, Na2O 2.8-3.5% and LOI 5.2-5.9%, ZrO2 0-0.6%, and other 0-0.6%.
[0078] For the above-mentioned ceramic plates with poor cutting performance, the present solution can also adjust the firing parameters of the ceramic plates to a maximum firing temperature of 1175-1185° C. and a firing time of 90-130 min.
[0079] For the ceramic plate with poor cutting performance, this solution can also adjust the green body expansion coefficient of the ceramic plate to 180-230*10 -6 / ℃; the glaze expansion coefficient of the ceramic plate is controlled at 170-220*10 -6 / ℃.
[0080] Example 4
[0081] Application of a method for evaluating cutting performance of ceramic plates in ceramic plate production:
[0082] The formula of the green body (green body raw materials) is adjusted to: 45 parts of low-temperature sand, 5 parts of ultra-white sand, 8 parts of bentonite, 3 parts of talc, 20 parts of ball clay, 12 parts of high-alumina sand, 5 parts of high-potassium stone and 2 parts of composite zirconium; the corresponding chemical composition is: SiO2 66.3%, Al2O3 21.4%, MgO 0.43%, CaO 0.47%, K2O 2.6%, Na2O 2.85% and LOI 5.62%, ZrO2 0.15%, and other (impurities) 0.18%;
[0083] The steps of making the above green body into a finished ceramic plate are as follows (the preparation process of Examples 1-11 also adopts the following steps):
[0084] The green body raw material is ball-milled to obtain slurry, which is then subjected to iron removal, sieving, aging, spray powdering and sieving to obtain green body, which is then pressed into shape by a large-tonnage press (a direct press of more than 15,000 tons); the green body after shaping is placed in a drying kiln for drying at a drying temperature of 120-150° C. (125° C. in this embodiment);
[0085] Apply the top glaze by pouring glaze, then use inkjet printing equipment for decorative printing, then use digital inkjet machine to spray digital protective glaze, and use glaze line drying equipment to dry the above products, and the temperature is controlled at 60-150° C. (100° C. in this embodiment);
[0086] The glaze is put into a kiln for firing, and the maximum firing temperature is adjusted from the initial 1150°C (the firing temperature of the original embodiment 1-11) to 1175°C, and the firing cycle is 100 minutes; after cooling, the edges are ground to obtain a finished ceramic plate.
[0087] Example 5
[0088] The preparation steps and parameters of the ceramic plate in this embodiment are consistent with those in Embodiment 4, with the only difference being that the formula of the ceramic plate is adjusted and the chemical composition is also changed.
[0089] 5-1: The formula is adjusted to 45 parts of low-temperature sand, 5 parts of super white sand, 4 parts of bentonite, 5 parts of talc, 22 parts of ball clay, 10 parts of high-alumina sand, and 9 parts of high-potassium stone. The chemical composition is: SiO2 66.99%, Al2O3 21.1%, MgO 0.32%, CaO 0.16%, K2O2.8%, Na2O 3.0% and LOI 5.63%.
[0090] 5-2: The formula is adjusted to 40 parts of low-temperature sand, 5 parts of ultra-white sand, 5 parts of bentonite, 1 part of talc, 30 parts of ball clay, 11 parts of high-alumina sand, and 8 parts of high-potassium stone. The chemical composition is: SiO2 65.74%, Al2O3 22.19%, MgO 0.06%, CaO 0.38%, K2O 2.75%, Na2O 3.08% and LOI 5.56%, and others (impurities) 0.24%.
[0091] 5-3: The formula is adjusted to 42 parts of low-temperature sand, 4 parts of super white sand, 4 parts of bentonite, 2 parts of talc, 27 parts of ball clay, 13 parts of high-alumina sand, and 8 parts of high-potassium stone. The chemical composition is: SiO2 67.21%, Al2O3 20.78%, MgO 0.15%, CaO 0.34%, K2O2.28%, Na2O 3.45% and LOI 5.25%, and others (impurities) 0.54%.
[0092] 5-4: The formula is adjusted to 45 parts of low-temperature sand, 5 parts of ultra-white sand, 1 part of bentonite, 5 parts of talc, 10 parts of ball clay, 15 parts of high-alumina sand, 18 parts of high-potassium stone and 1 part of composite zirconium. The chemical composition is: SiO2 65.8%, Al2O3 20.67%, MgO 0.66%, CaO0.85%, K2O 4.16%, Na2O 2.14% and LOI 5.26%, ZrO2 0.15%, and others (impurities) 0.31%.
[0093] 5-5: The formula is adjusted to 42 parts of low-temperature sand, 3 parts of super white sand, 3 parts of bentonite, 3 parts of talc, 15 parts of ball clay, 18 parts of high-alumina sand, and 16 parts of high-potassium stone. The chemical composition is: SiO2 66.02%, Al2O3 22.05%, MgO 0.41%, CaO 0.45%, K2O 2.52%, Na2O 2.43% and LOI 5.87%, others (impurities) 0.25%.
[0094] The specific correspondence between water absorption rate, vertical center curvature and cutting cracking rate is shown in the following table. This scheme also cuts 40 ceramic plates in each group mentioned above and records the actual cutting cracking situation:
[0095]
[0096] Note: Due to the slight difference in the predicted ranges of water absorption and center curvature, the actual cutting cracking rate is basically distributed in the overlapping range of the two. For example, in Example 5-4, the cutting cracking rate evaluated by water absorption is 15-30%, and the cutting cracking rate evaluated by center curvature is 20-50%, so the actual cutting cracking rate is generally around 20-30%.
[0097] It can be seen from the test results in the above table that after adjusting the formula (and chemical composition) of the ceramic plate with poor cutting performance, the cutting performance of the ceramic plate is improved.
[0098] After optimizing the chemical composition of this solution, the water absorption rate of the obtained ceramic plate can be controlled at 0.15% or less, and the vertical center curvature can be controlled below 1.5 mm, which can minimize the problem of cutting cracks.
[0099] Example 6
[0100] The preparation steps and parameters of the ceramic plate in this embodiment are consistent with those in Embodiments 1-11, with the only difference being that the firing system of the ceramic plate is adjusted, as shown in the following table:
[0101]
[0102]
[0103] The specific correspondence between water absorption rate, vertical center curvature and cutting cracking rate is shown in the following table. This scheme also cuts 40 ceramic plates in each group mentioned above and records the actual cutting cracking situation:
[0104]
[0105] As above, the actual cutting cracking rate is basically distributed in the overlapping range of the cutting cracking rate range evaluated by water absorption and the cutting cracking rate range evaluated by center curvature. For example, in Example 6-1, the cutting cracking rate evaluated by water absorption is 30-50%, and the cutting cracking rate evaluated by center curvature is 20-50%, so the actual cutting cracking rate is generally in the range of 30-50%.
[0106] It can be seen from the test results in the above table that after adjusting the maximum firing temperature of the ceramic plate with poor cutting performance, the cutting performance of the obtained ceramic plate can also be improved. The preferred maximum firing temperature is 1175-1185°C, at which time the ceramic plate has better cutting performance.
[0107] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for evaluating the cutting performance of a ceramic plate, characterized in that: The following steps are involved: S1. Detecting the vertical center curvature of the ceramic plate; S2. Grinding the ceramic plate to thin it, and detecting the water absorption rate of the ceramic plate after the grinding and thinning process; S3. Obtain the cutting cracking rate of the ceramic plate according to the water absorption rate of the ceramic plate and / or the vertical center curvature of the ceramic plate.
2. A method for evaluating cutting performance of a ceramic plate as claimed in claim 1, characterized in that: When the water absorption rate of the ceramic plate after grinding is ≤0.15%, the cutting cracking rate Q of the ceramic plate is ≤5%; When the water absorption rate of the ceramic plate after grinding is less than 0.15% and less than 0.2%, the cutting cracking rate Q of the ceramic plate is 5-15%; When the water absorption rate of the ceramic plate after grinding is less than 0.27%, the cutting cracking rate Q of the ceramic plate is 15-30%; When the water absorption rate of the ceramic plate after grinding is less than 0.27% and less than 0.35%, the cutting cracking rate Q of the ceramic plate is 30-50%; When the water absorption rate of the ceramic plate after being ground thin is ≥0.35%, the cutting cracking rate Q of the ceramic plate is >50%.
3. A method for evaluating cutting performance of a ceramic plate according to claim 1, characterized in that: When the vertical center curvature of the ceramic plate is ≤1.5mm, the cutting cracking rate Q of the ceramic plate is ≤5%; When the vertical center curvature of the ceramic plate is less than 1.5 mm and less than 2.0 mm, the cutting cracking rate Q of the ceramic plate is 5-20%; When the vertical center curvature of the ceramic plate is 2.0 mm or less and the cutting cracking rate Q of the ceramic plate is 20-50%; The vertical center curvature of the ceramic plate is ≥2.5mm, and the cutting cracking rate Q of the ceramic plate is >50%.
4. A method for evaluating cutting performance of a ceramic plate according to claim 1, characterized in that: In step S1, after the ceramic plate is ground thin, the water absorption rates at the four corners and the center are detected, and the average value is the water absorption rate of the ceramic plate.
5. The method for evaluating the cutting performance of a ceramic plate according to claim 1, characterized in that: In step S1, the front and back sides of the ceramic plate are both ground thinner by 1-3 mm.
6. The method for evaluating cutting performance of a ceramic plate according to claim 1, characterized in that: The area of the ceramic plate is 2m 2 above.
7. An application of the evaluation method according to any one of claims 1 to 6 in the production of ceramic panels, characterized in that: When the water absorption rate of the ceramic plate after grinding is ≥0.35%, or the vertical center curvature of the ceramic plate is ≥2.5mm, the formula of the ceramic plate is adjusted to: 40-60 parts of low-temperature sand, 3-5 parts of ultra-white sand, 3-8 parts of bentonite, 0-8 parts of talc, 20-35 parts of ball clay, 10-18 parts of high-alumina sand, 2-15 parts of high-potassium stone and 0-2 parts of composite zirconium.
8. The use according to claim 7, characterized in that The chemical composition of the ceramic plate is, by mass percentage, SiO2 65.5-67.3%, Al2O3 20.7-22.2%, MgO 0.06-0.5%, CaO 0.1-0.5%, K2O 2.2-2.9%, Na2O 2.8-3.5%, LOI 5.2-5.9% and ZrO2 0-0.6%.
9. The use according to claim 7, characterized in that When the water absorption rate of the ceramic plate is ≥2.5mm, or the vertical center curvature of the ceramic plate is ≥2.5mm, the firing parameters of the ceramic plate are synchronously adjusted to a maximum firing temperature of 1175-1185°C and a firing time of 90-130min.
10. The use according to claim 7, characterized in that When the water absorption rate of the ceramic plate is ≥2.5mm, or the vertical center curvature of the ceramic plate is ≥2.5mm, the green expansion coefficient of the ceramic plate is adjusted to 180-230*10 -6 / ℃; the glaze expansion coefficient of the ceramic plate is controlled at 170-220*10 -6 / ℃.
